2006
DOI: 10.1128/jcm.44.4.1453-1458.2006
|View full text |Cite
|
Sign up to set email alerts
|

Can the fliC PCR-Restriction Fragment Length Polymorphism Technique Replace Classic Serotyping Methods for Characterizing the H Antigen of Enterotoxigenic Escherichia coli Strains?

Abstract: In this study, we performed fliC PCR-restriction fragment length polymorphism (RFLP) to investigate whether this technique would be better than classic serotyping for the characterization of the H antigen in enterotoxigenic Escherichia coli (ETEC) strains. We showed that the fliC genes from ETEC strains can be characterized by restriction analysis of their polymorphism. Only one allele of the fliC gene from ETEC strains was found for each flagellar antigen, with the exception of H21. Nonmotile strains could al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 17 publications
(12 reference statements)
1
2
0
4
Order By: Relevance
“…Similar to reference strain E32511, H types were still obtained by WGS for the remaining six NM isolates that neither serotyping nor MS-H could identify. This further confirmed that H antigens characterized by WGS do not necessarily represent phenotypic H types, as genes responsible for flagellum production are not always expressed ( 27 ).…”
Section: Resultssupporting
confidence: 59%
“…Similar to reference strain E32511, H types were still obtained by WGS for the remaining six NM isolates that neither serotyping nor MS-H could identify. This further confirmed that H antigens characterized by WGS do not necessarily represent phenotypic H types, as genes responsible for flagellum production are not always expressed ( 27 ).…”
Section: Resultssupporting
confidence: 59%
“…Although the H type can be a useful phenotypic marker for classifying strains, we could not determine the H type of some O103 isolates, because of unclear agglutination or lack of bacterial motility. As many researchers have shown before (8,18,29), sequence variation in the fliC gene could be a proxy for these agglutination tests. In the present study, on the basis of sequence variation in fliC genes, we developed a multiplex PCR method for such classification of STEC O103 strains.…”
Section: Discussionmentioning
confidence: 99%
“…Herein we propose two new, original tools that can be useful for genotyping of E. coli isolates. The first of the developed method, a PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) test uses a highly variable fliC gene [8][9][10], encoding the H antigen as a molecular target. The second approach is based on the PCR amplification of seven selected genes that characterize with high sequence and size variability within the sequenced genomes of E. coli [11].…”
Section: Introductionmentioning
confidence: 99%